The Bacteria on Saliva of Diabetes Mellitus Patients in Arifin Achmad General Hospital, Riau Province (Future Science, 2022)
Diabetes Mellitus (DM) is a chronic non-communicable disease often found in the community. Patients with long-standing diabetes and uncontrolled blood glucose cause high salivary glucose levels and decreased salivary flow. This can be a medium for the growth and development of bacteria that can cause discomfort and various infections in the oral cavity. This research to know the characteristics of DM patients and the description of bacteria in the saliva of DM patients. The study was conducted by consecutive sampling method on DM patients who signed the informed consent, saliva samples were taken at the Arifin Achmad General Hospital, and the Microbiology Laboratory Faculty of Medicine, Universitas Riau for in vitro culture and identification of bacteria. Data processing is done manually and reported in the form of a frequency distribution table, expressed in percentages. The characteristics of research subjects from 30 samples obtained 14 men (46.66%), 16 women (53.33%), aged 33-67 years, elementary education 3 people (10%), junior high school 0 people (0%), high school 14 people (46.66%), PT 13 people (43.33%). DM status was controlled in 24 people (80%), and in uncontrolled 6 people (20%). The types of bacteria identified were Streptococcus sp 7 samples (17.5%), Streptococcus alpha hemolytic 2 samples (5%), Negative Coagulase Staphylococcus (CNS) 15 samples (37.5%), Staphylococcus aureus 2 samples (5%), Klebsiella sp 14 samples (35%). The conclusion of the research subjects are 33-67 years old, and most are women, with high school education, and controlled DM status. The most bacteria were Coagulase Staphylococcus (CNS) and Klebsiella sp.